Familial risks of second primary cancers and mortality in ovarian cancer patients - Zheng, Guoqiao; Chattopadhyay, Subhayan; Försti, Asta; Hemminki, Kari (Clinical epidemiology, 2018)
Familial risks of second primary cancers and mortality in ovarian cancer patients Guoqiao Zheng,1,2 Subhayan Chattopadhyay,1,2 Asta Försti,1,3 Kristina Sundquist,3–6 Kari Hemminki1,3 1Division of Molecular Genetic Epidemiology, German Cancer Research Center (DKFZ), Heidelberg, Baden-Württemberg, Germany; 2Faculty of Medicine, University of Heidelberg, Heidelberg, Baden-Württemberg, Germany; 3Center for Primary Health Care Research, Lund University, 205 02 Malmö, Skåne County, Sweden; 4Department of Family Medicine and Community Health, 5Department of Population Health Science and Policy, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 6Center for Community-Based Healthcare Research and Education (CoHRE), Department of Functional Pathology, School of Medicine, Shimane University, Izumo, Japan Background: With improving survival in ovarian cancer, second primary cancers (SPCs) and their etiological foundations are becoming an issue. The ways in which family history may influence the occurrence of SPCs and the related mortality are not well known. Methods: Based on the Swedish Family-Cancer Database, we identified 11,300 ovarian cancer patients and followed them for diagnoses of SPCs until the end of 2015. Relative risks (RRs) of SPC in patients who had parents or siblings diagnosed with the same cancer (positive family history) were compared to those in patients without a family history (negative family history). Causes of death were compared between patients with and without SPC. Results: A total of 1,111 (9.8%) ovarian cancer patients developed SPC with a median follow-up of 8 years. The impact of a family history of cancer on the risk of the same cancer as SPC was significant for colon (RRpositive family history [95% CI] vs RRnegative family history [95% CI]: 4.95 [3.03–8.09] vs 2.00 [1.63–2.47]), lung (3.32 [1.88–5.84] vs 1.45 [1.16–1.83]), and breast (2.08 [1.58–2.73] vs 1.01 [0.88–1.15]) cancers. With a family history of any cancer, the RR for non-ovarian SPCs was 1.66 (1.54–1.74), in contrast to 1.38 (1.24–1.54) for SPCs without any family history (P-trend <0.001). Accounting for 42.1% of all deaths, SPC was found to be the main cause of death for patients with SPC. Conclusion: A family history of a particular cancer contributed to an increased risk of SPC at the same site. Therefore, considering family history at the time of diagnosis of ovarian cancer may alert physicians to a syndromic background, management of which may help the patient and her family members. Keywords: second primary cancer, familial cancer, cause of death, cumulative incidence